High-resolution correlation of the Homerian carbon isotope excursion (Silurian) across the interior of the Midland Platform (Avalonia), UK. (29th April 2020) - Ray, David C.; Jarochowska, Emilia; Röstel, Philipp; Worton, Graham; Munnecke, Axel; Wheeley, James R.; Boomer, Ian
Abstract: New δ 13 Ccarb and microfacies data from Hereford–Worcestershire and the West Midlands allow for a detailed examination of variations in the Homerian carbon isotope excursion (Silurian) and depositional environment within the Much Wenlock Limestone Formation of the Midland Platform (Avalonia), UK. These comparisons have been aided by a detailed sequence-stratigraphic and bentonite correlation framework. Microfacies analysis has identified regional differences in relative sea-level change and indicates an overall shallowing of the carbonate platform interior from Hereford–Worcestershire to the West Midlands. Based upon the maximum δ 13 Ccarb values for the lower and upper peaks of the Homerian carbon isotope excursion (CIE), the shallower depositional setting of the West Midlands is associated with values that are 0.7 ‰ and 0.8 ‰ higher than in Hereford–Worcestershire. At the scale of parasequences the effect of depositional environment upon δ 13 Ccarb values can also be observed, with a conspicuous offset in the position of the trough in δ 13 Ccarb values between the peaks of the Homerian CIE. This offset can be accounted for by differences in relative sea-level change and carbonate production rates. While such differences complicate the use of CIEs as a means of high-resolution correlation, and caution against correlations based purely upon the isotopic signature, it is clear that a careful analysis of the depositional environment can account for such differences and thereby improve the use of carbon isotopic curves as a means of correlation.